Trends of Vaginal Birth after Cesarean Delivery in Germany from 1990 to 2012: A Population-based Study - Kyvernitakis, I.; Reichelt, J.; Kyvernitakis, A.; Misselwitz, B.; Hadji, P.; Schmidt, S.; Kalder, M. (Zeitschrift für Geburtshilfe und Neonatologie, 2014)
Background: The increasing incidence of cesarean deliveries (CD) in the western world is consequently leading to a rising number of antenatal counselling of pregnant women with a history of previous CD. To counteract the increasing trend of cesarean deliveries, the concept of vaginal birth after cesarean delivery (VBAC) may represent an alternative. The aim of the present study was to longitudinally investigate the incidence of VBAC and compare the changes within all deliveries during 23 years of follow-up.Methods: In this study we analyzed data from 1 202 557 deliveries in Hesse, Germany from 1990 to 2012. In total, 131 629 births have been identified to have at least one CD in the patients’ medical history. We grouped the patients into 3 categories: vaginal spontaneous birth subsequent to CD, vaginal-operative birth subsequent to CD and repeated CD.Results: After previous CD, 32.1% of the patients delivered spontaneously, 4.0% delivered vaginal-operative and 63.8% had a repeated CD. The rates changed from 40.4, 7.5 and 52.1% in the year 1990 to 23.3, 2.8 and 73.9% in the year 2012 for vaginal spontaneous births, vaginal-operative births and for repeated CDs, respectively (p<0.01). We noticed a decline of 17.1 and 4.7% in spontaneous births after Cesarean and vaginal operative births respectively during the observation period. Notably, we report a dramatic increase of 21.8% of repeated CDs during the past 23 years (p<0.01). With regard to the non-affected group including all deliveries, we observed a decrease of 17% in spontaneous deliveries from 1990 to 2012 (75.9 vs. 58.9%). Vaginal operative delivery rates changed from 6.9% in 1990 to 5.9% in 2012. Consequently, CD rates increased from 17.2% in 1990 to 35.2% in the year 2012 (p<0.01). The differences between all 3 subgroups were significantly different (p<0.001).Discussion: Cesarean rates in Germany have reached an all-time high, while VBAC follows a continuous decrease. The current rate of VBAC is almost the half of that in the year 1990 (26.1 vs. 47.9%). Promotion of a trial of labor (TOL) after low transverse CD in those women who desire 3 or more children may increase the VBAC success rates and reduce maternal morbidity.
Keywords: incidence; Cesarean; vaginal birth after Cesarean; delivery mode